Bahasa Inggris - M. Firdaus Imaduddin; Bahruddin, Uril (Jurnal Al-Maqoyis, 2025)
AI advancements have revolutionized Arabic language learning through applications like Busuu, AlifBee, and Arabits, offering interactive and personalized experiences. This study examines the similarities and differences in their content organization, teaching strategies, and technological features using a qualitative, comparative approach. The findings of this research are: (1) The applications share similarities in organizing educational content, such as covering Arabic alphabets, grammatical diacritics, and daily life themes, as well as employing common patterns in exercises and tests. However, they differ significantly in teaching methodologies and available technologies. Busuu relies on the Common European Framework of Reference for Languages (CEFR), Arabits adopts a curriculum tailored to the UAE context, and AlifBee is based on Modern Standard Arabic. (2) The applications use interactive strategies that emphasize gamification and the development of the four linguistic skills, but they diverge in unique features: Busuu incorporates global community interaction and certifications from McGraw-Hill Education, Arabits employs strategies like "City Exploration" and "Vocabulary Cards," while AlifBee offers elective courses and Pearson-certified credentials. (3) The applications all utilize AI technologies, such as NLP, multimedia content, and user progress tracking. However, Busuu and AlifBee stand out with smart review features, Arabits integrates advanced machine learning and deep learning algorithms, and AlifBee further enhances its offerings with phonetic and textual features.